Analysis of The Influence Between Turbidity Value on Total Suspended Solid (TSS) Value At The River Water Surface In Kutai Kartanegara - Alya Indah Putri; Meidi Arisalwadi (Frontier Advances in Applied Science and Engineering, 2023)
Indonesia is a country that has abundant natural resources, one of which is non-renewable natural resources such as minerals and coal. One of the provinces in Indonesia that has natural wealth of minerals and coal is in the province of East Kalimantan, one of which is in Kutai Kartanegara Regency. The coal mines also use rivers to carry out their mining activities such as exploiting mining products. physical parameters for water quality color, odor, temperature, solids, TDS, TSS, oil and grease. The value of Turbidity and TSS is always directly proportional or linear because it is supported by a theory which states that the value of TSS is always directly proportional to the value of Turbidity, because the higher the TSS or solid particles, the higher the value of Turbidity, resulting in linearity.